2018
DOI: 10.2478/bog-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based tourism operators’ perceptions and adaptation to climate change in Hwange National Park, Zimbabwe

Abstract: How to cite: Mushawemhuka W., Rogerson J.M. and Saarinen J., 2018: Nature-based tourism operators' perceptions and adaptation to climate change in Hwange National Park, Zimbabwe.Abstract. Climate and weather are important resources for tourism. In particular, nature-based tourism activities and operations are largely dependent on and affected by environmental conditions and changes. Due to the significant socio-economic role of the nature-based tourism and the tourism industry, in general, in the region of sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…3.6. The 'other big story'debating tourism and climate change after Prior to the onset of the global COVID-19 pandemic, the 'big ticket' research topic in tourism for Africa and, globally, was creating a responsible and sustainable future for tourism that meets international targets designed to reduce the impact of climate change (Rogerson, 2016;Sifolo & Henama, 2017;Mushawemhuka et al, 2018;Pandy & Rogerson, 2019. The shutdown of travel within and to Africa (alongside the halt to other areas of economic activity), caused by response to COVID-19 has demonstrated the environmental benefits of limiting the polluting effects of some forms of tourism, most visibly in cities such as Venice.…”
Section: Informal Sector Resiliencementioning
confidence: 99%
“…3.6. The 'other big story'debating tourism and climate change after Prior to the onset of the global COVID-19 pandemic, the 'big ticket' research topic in tourism for Africa and, globally, was creating a responsible and sustainable future for tourism that meets international targets designed to reduce the impact of climate change (Rogerson, 2016;Sifolo & Henama, 2017;Mushawemhuka et al, 2018;Pandy & Rogerson, 2019. The shutdown of travel within and to Africa (alongside the halt to other areas of economic activity), caused by response to COVID-19 has demonstrated the environmental benefits of limiting the polluting effects of some forms of tourism, most visibly in cities such as Venice.…”
Section: Informal Sector Resiliencementioning
confidence: 99%
“…The latter study disclosed that even though the majority of entrepreneurs believed climate change would impact the tourism industry, less than half of the respondents considered it might affect their own businesses (Tervo-Kankare et al, 2018). Mushawemhuka et al (2018) investigate nature tourism operators' perceptions and adaptations to climate change in Hwange National Park, Zimbabwe.…”
Section: Tourism and Climate Change Perceptionsmentioning
confidence: 99%
“…Tourists to South Africa are potentially sensitive to high temperatures (Giddy, Fitchett & Hoogendoorn 2017), and in Kruger National Park the annual average maximum temperature has increased from around 29 °C to over 31 °C since the 1970s (Dube & Nhamo 2020). A series of mixed-methods studies involving semi-structured interviews have shown that rising temperatures and drought have already impacted on tourism experiences in flagship parks of the region such as Kruger National Park, Victoria Falls, the Okavango Delta and the Hwange National Park (Dube & Nhamo 2018Mushawemhuka et al 2018), as well as in private nature reserves (Smith & Fitchett 2020). These conclusions are supported by empirical evidence of the negative impact of drought on numbers of visitors in Kruger National Park (Mathivha, Tshipala & Nkuna 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The temperature models explained over 50% of the variance in historical occupancy for 17 parks, suggesting that climate change may have a significant impact on the timing and magnitude of demand across the network. Based on projected future temperatures, the region (Dube & Nhamo 2018MacFadyen et al 2019;Mushawemhuka, Rogerson & Saarinen 2018;Sutherland, Ndlovu & Pérez-Rodríguez 2018). This study extends the existing literature by undertaking an empirical analysis of the sensitivity of park tourism to temperature, based on historical data.…”
Section: Introductionmentioning
confidence: 97%